PENINJAUAN KEMBALI DALAM PERKARA PIDANA YANG BERKEADILAN DAN BERKEPASTIAN HUKUM - Arfan Faiz Muhlizi (Komisi Yudisial RI, 2015)
ABSTRAKPutusan Mahkamah Konstitusi (MK) Nomor 34/PUUXI/2013 pada prinsipnya membolehkan peninjauan kembali (PK) dilakukan lebih dari satu kali. PutusanMK tersebut menyatakan Pasal 268 ayat (3) Undang-Undang Nomor 8 Tahun 1981 tentang Hukum Acara Pidana yang berbunyi “Permintaan peninjauan kembali atas suatu pemutusan hanya dapat dilakukan satu kali saja,” tidak mempunyai kekuatan hukum mengikat. Pasca putusan tersebut, Mahkamah Agung (MA) justru menerbitkan Surat Edaran Mahkamah Agung (SEMA)Nomor 7 Tahun 2014 tentang Pengajuan Permohonan Peninjauan Kembali dalam Perkara Pidana, yang menyatakan bahwa permohonan peninjauan kembalidalam perkara pidana dibatasi hanya satu kali. Hal ini menimbulkan kebingungan bagi aparat penegak hukum dan masyarakat pencari keadilan. Tulisan ini mengkaji solusi atas polemik peninjauan kembali dalam perkara pidana. Pembahasannya diawali dengan pemenuhan unsur keadilan dan kepastian hukum dalam PK seiring terbitnya Putusan MK dan SEMA tersebut. Pembahasanselanjutnya mengenai apakah pengaturan upaya PK selaras dengan prinsip perlindungan HAM. Dalam analisis disimpulkan bahwa: 1) pemenuhan keadilan (doelmatigheid) dalam upaya PK harus dilaksanakan dengan bingkai kepastian hukum (rechtmatigheid); 2) Putusan MK telah memberikan perlindungan HAM danselaras dengan Statuta Roma 1998, yang memberikan kesempatan seluas-luasnya untuk mengajukan koreksi dan rekoreksi terhadap putusan yang dipandang tidak adil; dan 3) dengan menggunakan asas res judicata pro veritatehabetur maka dasar pengajuan PK harus berpedoman pada Putusan MK. Selanjutnya yang perlu dilakukan adalah membuat mekanisme untuk mempercepat proses pemeriksaan PK dan mempercepat eksekusinya.Kata kunci: peninjauan kembali, keadilan, kepastian hukum. ABSTRACTThe Constitutional Court Decision Number 34/PUU-XI/2013 principally approves the petitioner’s extraordinary request for review more than once. The court decision argues that Article 268 paragraph (3) of Law Number 8 of 1981 regarding Code of Criminal Procedure which states, “the petition for extraordinary request for review a court decision shall only been filed once,” does not have a binding legal force. After the issuance of the decision, the Supreme Court in point of fact releases the Circular Letter of the Supreme Court (SEMA) Number 7 of 2014 concerning the ExtraordinaryRequest for Review Petition in Criminal Cases, settling that the petitioner’s extraordinary request for review in criminal cases filed more than once is unacceptable and not in line with the law. This leads to confusion for law enforcement officials and justice seekers. Therefore, this analysis brings forth the resolution to the polemical notion of the Extraordinary Request for Review Petition in criminal cases. The discussion is started by the fulfillment of the element of justice and legal certainty in the Extraordinary Request for Review Petition in keeping with the Supreme Court’s Circular Letter, and subsequently on whether the preparation of the petitionof case review has been aligned with the principles of human rights protection. The analysis comes to resolve that: 1) the fulfillment of justice (doelmatigheid) in theExtraordinary Request for Review Petition shall be implemented through the framework of legal certainty (rechtmatigheid); 2) the decision of Constitutional Courthas provided human rights protection complying to the Rome Statute of 1998, which give the widest possible opportunity to apply for correction and re-correction ofthe decision deemed unjust; and 3) in accordance with the principle of “res judicata pro veritate habetur,” the Extraordinary Request for Review Petition shall referto the Constitutional Court’s Decision. The next step is to create a mechanism to speed up the process of examination of the review and accelerate the execution.Keywords: extraordinary request for review petition, justice, legal certainty.